PENGARUH KOMPETENSI, PROGRAM DIKLAT, DAN MOTIVASI KERJA TERHADAP PENINGKATAN KINERJA KARYAWAN PT. BPR NUR SEMESTA INDAH KABUPATEN JEMBER - Muttaqien, Fauzan; Fitria, Novy; Rizki, Via Lailatur; Abrori, Imam (Jurnal Istiqro, 2025)
This study aims to analyze the influence of competence, training programs, and work motivation on employee performance at PT. BPR Nur Semesta Indah, Jember Regency. This type of research is quantitative. The number of research samples is 50 respondents, namely, employees of PT. BPR Nur Semesta Indah, Jember Regency. Primary data collection through filling out questionnaires. The data analysis method is carried out using multiple linear regression analysis. Instrument testing uses normality test, multicollinearity test, and heteroscedasticity test, model feasibility test uses F-test, multiple determination coefficient, and hypothesis test uses t-test. The results of the study indicate that the Competence variable has a positive and significant effect on employee performance at PT. BPR Nur Semesta Indah, Jember Regency, the training program variable does not affect employee performance at PT. BPR Nur Semesta Indah, Jember Regency. Work motivation has a significant effect on employee performance at PT. BPR Nur Semesta Indah, Jember Regency.